A Feasibility Study on RGR Retreading Company - Baligod, Robin; Bernales, Rolando Jr.; Sabareza, Genaline (Diliman, Quezon City College of Engineering, 1997)
This paper presents the feasibility of servicing old tires as substitute for brand new ones. This process is known as RETREADING. The carcass of the tire is capped with a new tread. The production process of tire retreading has twenty operations that make the performance of a retreaded beyond compare. Demand for retreaded tires greatly exceeds supply. The demand has been increasing for the past years. The demand for the next five is above two hundred thousand per year. The target market shares of the group for the next five years are 15,16,17,18 and 20% respectively. The technical study evaluated several alternatives regarding the production plans. Four alternatives were presented regarding labor requirements and machine requirements that would meet the target demand. The following are the conclusions derived from the technical analysis: *The production shift will be eight hours per day, 24 days per month. *The total production workers needed is 42. *The total number of equipment to be purchased is 37. *The plant will be located at Commonwealth Avenue cor. Akasya St, Fairview, Quezon City. *The suppliers of raw materials are Ramko, Mared Rubber and Marketing Corporation and Johnstown Trading *The design of the plant layout. After the technical matters have been finalized, it was decided that a partnership of organization will be employed. The financial study is ready; the different financial statements were prepared. It is clear and evident from the positive increasing net income and the positive cash flows each year that the project is financially profitable. The net income for the next five are P7,215,920.61, P9,819,956.19, P15,607,689.18 and P20,772,783.59 respectively. The payback period is four years and four months time. The internal rate of return was computed to be 23% and a large positive net present value was also computed, this proves that the project is acceptable and an attractive venture. The type of ownership that the company will adopt will be a partnership. Five partners will compose the company. A total of 29 office personnel will be hired by the company. Numerous advantages were enumerated in the social profitability analysis. The beneficiaries include the government, the surrounding communities in the vicinity of the plant, and the related industries. The income tax for 1998 alone is P6,817,612.85 and VAT is P5,151,771.81, The city tax is worth P257,588.59 for the first year of operation. Real state tax which the city government will also collect is P36,000. Raw materials suppliers will also benefit from the project. For the first year alone, the cost of raw material to be purchased by the company is worth P10,321,678.20 From these facts, the social profitability of the project is acceptable. In conclusion, the project is feasible and would prove to be profitable, too.
Feasibility Study
Submitted in partial fulfillment of the course requirements in IE 153 : Project Development and Management
Keywords: RGR Retreading Company; Tires; Tires--Retreading and recapping; Participatory monitoring and evaluation (Project management)